How to Reproduce in the Siberian Winter: Proteome Dynamics Reveals the Timing of Reproduction‐Related Processes in an Amphipod Species Endemic to Lake Baikal - Polina Lipaeva; Polina Drozdova; Kseniya Vereshchagina; Lena Jakob; Kristin Schubert; Daria Bedulina; Till Luckenbach (Ecology and Evolution)
ABSTRACT The winters in the region of the vast global freshwater biodiversity hotspot Lake Baikal are extremely cold. Although the conditions for reproduction may seem unfavorable during winter, the lake is inhabited by a major endemic winter‐reproducing amphipod species complex. Compared with Baikal's summer‐reproducing amphipod species, the duration of a reproduction cycle in the winter‐reproducing species is more extended. We hence hypothesized that in those species, reproduction‐related processes dependent on external resources are scheduled to occur outside of winter when the conditions are more advantageous. To receive insights into the ongoing processes, we analyzed sex‐specific seasonal proteome dynamics in Eulimnogammarus verrucosus as a representative of the winter‐reproducing amphipod species. Individuals of the species were collected during five field samplings from the beginning of fall to the following summer (2019/2020) and their proteomes were analyzed. Especially, the female proteomes were dominated by sampling time point‐specific hallmarks of reproduction‐related processes and events. It was evident that the formation of the oocytes in female E. verrucosus already took place in the summer. Embryo development, not depending on external resources but fueled by the yolk reserves in the egg, proceeded over the winter, and juveniles hatched from the eggs in the following spring. Adjustments of the amphipods of both sexes to environmental winter conditions were reflected by abundance changes of digestive system‐related enzymes, indicating a proteome response to seasonal diet changes, and of enzymes involved in RNA biosynthesis, protein folding, and homeoviscous adaptation processes, possibly related to decreasing water temperatures. The characteristics of the proteome dynamics revealed here, set in relation to season‐specific environmental parameters, indicate a strategy of a cold‐adapted amphipod to cope with the unique and extreme environmental conditions of Baikal, which is directed to the pace and timing of the resource‐dependent reproduction‐related processes.